PENERAPAN PEMBELAJARAN JIGSAW DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN GEOGRAFI DI SMA NEGERI 1 REMBOKEN - Tumembouw, Anastaysa Natalia Jusia; Lobja, Xaverius Erick; Rifani, Irfan; Selfiardy, Syafrida; Korompis, Emanuel Estefanus; Nugroho, Cahyadi (Jurnal Social Science, 2025)
The main research problem is how the use of Jigsaw learning can improve students learning outcomes in geography subjects at SMA Negeri 1 Remboken The research objective is to determine the use of Jigsaw learning to enhance students learning outcomes in geography subjects at SMA Negeri 1 Remboken < em> The research method employed is descriptive quantitative research with data collection techniques including observation documentation interviews and tests as the main techniques The sampling method used is purposive sampling The research respondents are 27 students from class Xb < em>The research findings indicate that: 1 The results of the learning activities show that the majority of students who participated in this research demonstrated good learning activities during the learning process 2 Most students who participated in this research showed successful participation in the learning activities resulting in good learning outcomes The data shows that students achieved a score of 70 with all 27 students 100 of the participants obtaining this score Therefore all students are considered successful in the Jigsaw learning they participated in < em>< p>